Effectiveness and safety of cervical ripening methods in the outpatient setting: a systematic review and network meta-analysis - Dorri, Mahya (My University, 2025)
Background: Cervical ripening (CR) involves preparing the uterine cervix for the initiation of labour. Outpatient CR is increasingly considered for low-risk pregnancies in the interest of patient satisfaction and reduced utilization of healthcare resources. However, there is no consensus on the optimal method for outpatient CR. Methods We conducted a systematic review and frequentist random-effects network meta-analysis (NMA) of randomized controlled trials (RCTs), to compare CR methods eligible for use in outpatient settings. We searched seven databases through January 2024, without date or language restrictions. Title/abstract screening, full-text review, data extraction, and risk of bias assessment (Cochrane RoB-2.0) were performed independently and in duplicate. We assessed the certainty of evidence using Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) approach. Although seven outcomes related to effectiveness, safety and resource use were identified, for purposes of this thesis, we only reported the analysis for the effectiveness outcome, which was defined as attaining a vaginal birth. Effect sizes were reported as odds ratios (OR) with 95% confidence intervals (95%CI). Results Our search identified 8490 studies, of which we included 51 RCTs reporting on 1504 pregnancies. We used the standard Foley catheter (FoleySt) as the reference treatment and defined 23 nodes. Oral misoprostol at high initial (more than 50 mcg) and high cumulative (more than 150 mcg) dose was the most effective treatment at achieving a vaginal birth (OR: 2.38; 95%CI: 1.02 to 5.56, RD: 132 more; 95% CI: 4 to 201 more per 1000 participants; moderate certainty evidence). Conclusion High-dose oral misoprostol was found to be the most effective CR method. However, these results should be interpreted in the context of safety and, resource-related outcomes, which remain to be studied.
Keywords: Cervical Ripening; Network Meta-analysis